Ground-Based Solar UV Radiation Monitoring Technique Using Photocell - Koirala, Paribesh; Tripathee, Raj K; Pandey, Nitesh (Journal of the Institute of Engineering, 2012)
This paper presents Solar UV radiation monitoring technique using a photo voltaic cell. The data obtained by such technique can be used to calculate the UV index and measure risk of UV exposure. UV irradiance at the surface is affected by the solar elevation, total ozone, clouds, aerosol, surface albedo etc. This paper presents results from the designed instrument to evaluate the UV index. The data obtained from such method will have benefit in installation, maintenance, data transfer and operational cost. This paper highlights the development and initial validation of standard UV data along with the portable embedded device for personalized UV monitoring which is based on a novel programming technique, photo Voltaic Cell as UV sensor, and a microcontroller PIC16F877A. This portable personalized UV monitoring device just provides the tentative UVI as it does not take the depth of ozone layer into account. Rough estimation of UVI can be obtained with such embedded system. DOI: http://dx.doi.org/10.3126/jie.v8i3.5943 JIE 2011; 8(3): 177-189